Health Behavior Constructs Scale (HBCS) for Breast Cancer Screening: Development, Validity and Reliability - Besharat, Mohammad Ali; Zarani, Fariba; Mazaheri Nejad Fard, Golnaz; Haji SeyedSadeghi, Maryam (International Journal of Applied Behavioral Sciences, 2021)
Introduction: Given the importance of screening as one of the health behaviors in breast cancer, the aim of this research is to develop and evaluate the psychometric characteristics of Health Behavior Constructs Scale (HBCS) for breast cancer screening.Methods: In this cross sectional study, 376 women who referred to Javaheri Health Center during the study period due to health problems, were selected through convenience sampling method. Then, the instrument was developed and its content and face validities were examined. To ensure divergent and convergent validity, Depression Anxiety Stress Scale (DASS-21) was used. Internal consistency method (Cronbach’s alpha) was used to determine the reliability of the questionnaire. Finally, confirmatory factor analysis was used to assess the construct validity of the Health Behavior Constructs Scale and SPSS and LISREL software were applied for analyzing data.Results: The findings of this study provided strong supports, which confirmed the content and face validities. Regarding the convergent and divergent validity, perceived vulnerability, perceived severity and deterioration, and perceived barriers have a direct and significant relationship with the three variables of depression, anxiety, and stress. On the other hand, perceived self-efficacy and perceived motivation had a significant inverse correlation with all three variables of depression, anxiety, and stress. The results of the Cronbach’s alpha indicated the appropriate internal consistency of the whole questionnaire and its components. Cronbach’s alpha for the whole questionnaire was 0.75. According to confirmatory factor analysis, the goodness of fit indicators of proposed model were confirmed and all paths were significant.Conclusion: HBCS is a reliable and valid tool for measuring the screening behavior of breast cancer in Iranian women and it appears to be a comprehensive and useful instrument for assessing women’s beliefs related to breast cancer and breast cancer screening.